PENERAPAN SAPTA PESONA PADA OBJEK WISATA PANTAI NATAL DI KABUPATEN MANDAILING NATAL PROVINSI SUMATERA UTARA - Lesfika, Adinda; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research was conducted to determine the application of Sapta Pesona and the obstacles in implementing Sapta Pesona at the Natal Beach tourist attraction. This research was conducted in Natal Village, Mandailing Natal district. The research method used in this research is descriptive qualitative. The research subjects were the Mandailing Natal District Tourism and Culture Office, the Natal Market II Community and Business Actors at Natal Beach. The data collection techniques used in this research are observation, interviews and documentation. The results of the research found that the Sapta Pesona elements that have been implemented at Natal Beach are: (1) safe elements, (2) orderly elements, (3) cool elements and (4) friendly elements. Meanwhile, three elements have not been implemented, namely: (1) clean elements, (2) beautiful elements, and (3) memorable elements. Keywords: Application, Sapta Pesona, and Natal Beach